Pemilihan Pemasok Dengan Mempertimbangkan Produksi Bersih/Green Manufacturing Pada Industri Otomotif - Johan K. Runtuk; Anastasia Lidya Maukar (Jurnal Rekayasa Sistem Industri, 2020)
This study aims to select the best suppliers based on Fuzzy-AHP and ELECTRE methods in multinational automotive companies in Indonesia. Fuzzy AHP method is used to determine the weight of criteria and sub-criteria in reducing uncertainty and unclear information. Meanwhile, the ELECTRE method is used to rank alternative suppliers. Both methods are used to reduce subjective decisions and improve the accuracy of selected suppliers. After applying Fuzzy AHP and ELECTRE methods, the supplier chosen for the steel fuel tank is S1, for side beam impact is S2, wheel disc is S2, Seat is S1, door trim is S2, lamp is S3, headlining is S3, insulator is S1 and hose is S3.Keywords: JIT, supplier performance, Fuzzy-AHP, ELECTRE